Parallel computing on heterogeneous Networks: Challenges and Responses - Lastovetsky, Al. (Інститут програмних систем НАН України, 2004)
In the paper, we analyse challenges associated with parallel programming for common networks of computers (NoCs) that are, unlike dedicated parallel computer systems, inherently heterogeneous and unreliable. This analysis results in description of main features of an ideal parallel program for NoCs. We also outline some recent parallel programming tools, which try and respond to some of the challenges.